Effects of a Goal-Oriented Intervention on Self-Management Behaviors and Self-Perceived Burden After Acute Stroke: A Randomized Controlled Trial - Chen, Yu; Wei, Yuanyuan; Lang, Hongjuan; Xiao, Ting; Hua, Yan; Li, Lu; Wang, Jing; Guo, Hongxia; Ni, Chunping (Frontiers in Neurology, 2021)
Background: Stroke generates significant health and social burdens. Self-management has potential importance for supporting individuals in coping and continuing to progress after stroke. However, there is a lack of targeted programs to enhance self-management and reduce self-perceived burden (SPB) following stroke. Purpose: To evaluate the effects of a goal-oriented intervention on self-management behaviors and SPB among patients after acute stroke. Methods: This was a randomized controlled trial with a 4-week intervention. Participants were randomly allocated to the goal-oriented intervention group (n=48) or control group (n=48). Self-management behaviors and SPB were evaluated and compared between the two groups. Results: After the one-month follow-up, there were significant differences in the total self-management behaviors score and the scores of six of the self-management dimensions, excluding diet management, between the intervention group and the control group (t=-7.891～-2.815; P≤0.006). Compared to the control group, the intervention group showed a significant decrease in the physical burden, emotional burden and total SPB scores (t=2.102～2.071; P=0.015～0.041). The economic burden score was not significantly different between the two groups (t=1.707; P=0.091). Conclusion: The goal-oriented intervention based on Pender’s health promotion model can effectively improve self-management behaviors and reduce physical and emotional SPB among stroke survivors.